270 Prevalence, prescriptions, outcomes and costs of type 2 diabetic patients with or without prior coronary artery disease or stroke: a longitudinal 5-year claims-data analysis of over 7 million inhabitants. (17th December 2020) - Calabria, Silvia; Dondi, Letizia; Andreotti, Felicita; Ronconi, Giulia; Piccinni, Carlo; Capponcelli, Anna; Pedrini, Antonella; Esposito, Imma; Martini, Nello; Maggioni, Aldo P
Abstract: Aims: Contemporary, real-world data on type 2 diabetes mellitus (T2DM) are limited. We analysed prevalence, comorbidities, outcomes and costs of T2DM patients with and without coronary artery disease (CAD) or stroke in > 7 million inhabitants. Methodsand results: T2DM patients were identified in 2015 (accrual period) from the Ricerca e Salute (ReS) database linking administrative records to demographics. From 2013 to 2015 information, four cohorts were considered: #1 with CAD and/or stroke; #2 without CAD and/or stroke; #3 with chronic CAD but no myocardial infarction or stroke; #4 with chronic CAD undergoing percutaneous coronary interventions (PCI). Hospitalizations, drugs and other outpatient care were assessed from 2015 to 2017. Prevalence of T2DM was 6% (441, 085/7, 365, 954). CAD and/or stroke in the previous 3 years affected 7.5% of T2DM patients (33, 153); this cohort was generally older, male, comorbid, with more prescriptions, hospital admissions (50% vs. 13.4%) and recurrences compared to cohort #2. Yearly costs were >3-fold for cohort #1 vs. #2, main drivers being hospitalizations in the former and drugs in the latter. Unexpectedly, two-year cardiovascular events were significantly higher in cohort #4 compared to any other. Guideline-recommended therapies were suboptimal in all. Conclusion: The present analysis points to three areas of potential improvement in T2DM management: (1) undertreatment of T2DM patients with recommended drugs; (2) three-fold event rates and costs in T2DM patients with, compared to those without, prior cardiovascular events; (3) highest risk of events in those with chronic CAD and PCI, warranting specific studies aimed at defining more effective preventive strategies.